miR-1207-5p and miR-1266 suppress gastric cancer growth and invasion by targeting telomerase reverse transcriptase - Chen, L (Nature Publishing Group, 2014)
hTERT is the catalytic subunit of the telomerase complex. Elevated expression of hTERT is associated with the expansion and metastasis of gastric tumor. In this study, we aimed to identify novel tumor suppressor miRNAs that restrain hTERT expression. We began our screen for hTERT-targeting miRNAs with a miRNA microarray. miRNA candidates were further filtered by bioinformatic analysis, general expression pattern in different cell lines, gain-of-function effects on hTERT protein and the potential of these effects to suppress hTERT 3′ untranslated region (3′UTR) luciferase activity. The clinical relevance of two miRNAs (miR-1207-5p and miR-1266) was evaluated by real-time RT-PCR. The effects of these miRNAs on cell growth, cell cycle and invasion of gastric cancer cells were measured with CCK-8, flow cytometry and transwell assays. Finally, the ability of these miRNAs to suppress the transplanted tumors was also investigated. Fourteen miRNAs were identified using a combination of bioinformatics and miRNA microarray analysis. Of these fourteen miRNAs, nine were expressed at significantly lower levels in hTERT-positive cell lines compared with hTERT-negative cell lines and five could downregulate hTERT protein expression. Only miR-1207-5p and miR-1266 interacted with the 3′ UTR of hTERT and the expression levels of these two miRNAs were significantly decreased in gastric cancer tissues. These two miRNAs also inhibited gastric tumor growth in vitro and in vivo. Altogether, miR-1207-5p and miR-1266 were determined to be hTERT suppressors in gastric cancer, and the delivery of these two miRNAs represents a novel therapeutic strategy for gastric cancer treatment.